Electrochromism in MoO3 nanostructured thin films. (August 2021) - Dixit, Divya; Madhuri, K.V.
Abstract: Molybdenum trioxide thin films were grown onto well cleaned Indium Tin Oxide coated glass substrate by Pulsed Laser Deposition technique in presence of oxygen partial pressure about 100 mTorr and at several substrate temperature (Ts ) ranging from 100 °C to 400 °C. Systematic characterisation of grown films is employed in order to study the growth of films, structure, optical and electrochromic properties. Presence of only Mo and O elements in Energy Dispersive Spectra of grown films stated that the films were pure without any contaminants. The films were showing mixed α and β phase at Ts = 100 °C and slowly turns to α-phase with rise of substrate temperature to 400 °C. The grain size was observed to be increased in the films deposited up to 300 °C which is supported by Scanning Electron Microscopic and Atomic Force Microscopic images. The variation in the optical transmittance, bandgap and electrochromic efficiency with respect to substrate temperature are clearly discussed in this research paper. Highlights of Research Work: MoO3 films were deposited by PLD technique under PO2 ≈100 mTorr at various substrate temperatures ranging from 100 °C–400 °C. The films deposited were found to be homogeneous, uniform and pure. The films showed mixed phase of α-β up to Ts = 200 °C and turns to α- phase from 300 °C. The optical bandgap values increased with substrate temperature up to 300 °C and then decreased for films deposited at 400 °C. The films exhibit maximum electrochromic efficiency for the films deposited at TS = 300 °C.